Novel variant c.92T > G (p.Val31Gly) in the PFN1 gene (ALS18) responsible for a specific phenotype in a large Bulgarian amyotrophic lateral sclerosis pedigree - Angelov, Teodor; Chamova, Teodora; Atemin, Slavena; Todorov, Tihomir; Ormandzhiev, Slavko; Tourtourikov, Ivan; Todorova, Albena; Devos, David; Tournev, Ivailo (Frontiers in Neurology, 2023)
Objectives: Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disorder characterized by progressive deterioration of motor function, disability, and death. Variants in the PFN1 gene, encoding the Profilin-1 protein, are related to ALS18. Methods: We present a pedigree consisting of 3 generations and 4 affected individuals, 3 of which carry a novel heterozygous variant: c.92T>G (p.Val31Gly) in the PFN1 gene. This variant was discovered through means of whole exome sequencing (WES) and targeted analysis of ALS-related genes. Results: The mean age of onset in our pedigree was 59.75 (±10.11 SD) years with a significant difference between the first two generations (females) and the third (male) of 22.33 (±3.4 SD) years. For this ALS form, we observed a longer disease progression of 4 (±1.87 SD) years (three of four affected are still alive). Clinical manifestations displayed predominant impairment of the lower motor neuron (LMN) in one limb, with gradual involvement of other limbs. A novel heterozygous missense variant c.92T>G, p. Val31Gly (NM_005022.4) in exon 1 in the PFN1 gene was discovered through means of whole exome sequencing (WES). Segregation analysis in the family showed that the detected variant was inherited from the affected mother, and the affected aunt also turned out to be a variant carrier. Conclusions: ALS18 is a very rare form of the disease. We report here a relatively large pedigree with a novel variant, leading to late onset (after 50 years), initial involvement of the lower limbs and relatively slow progression.